1974
DOI: 10.1111/j.1365-2125.1974.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Hydroxylation of Amylobarbitone Sodium in Man

Abstract: 1Following a single oral dose of amylobarbitone sodium it has been shown that a group of young subjects convert a higher proportion of the dose to 3'-hydroxyamylobarbitone than a group of elderly subjects. 2 Twenty-four hours after the administration of the drug, the mean plasma level of amylobarbitone in the elderly group is significantly higher than in the group of young subjects. 3 It is concluded that the rate of hydroxylation of amylobarbitone sodium decreases with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…(Figure 2). Larodopa reached equilibrium concentrations between 20 and (Shy & Drager, 1960 Stevenson, 1971;Irvine, Grove, Toseland & Trounce, 1974;Castleden, Kaye & Parsons, 1975), and hepatic function in the Parkinsonian age group (Thompson & Williams, 1965) are impaired.…”
Section: Resultsmentioning
confidence: 99%
“…(Figure 2). Larodopa reached equilibrium concentrations between 20 and (Shy & Drager, 1960 Stevenson, 1971;Irvine, Grove, Toseland & Trounce, 1974;Castleden, Kaye & Parsons, 1975), and hepatic function in the Parkinsonian age group (Thompson & Williams, 1965) are impaired.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise Streicher & Garbus (1955) showed that hexobarbitone sleeping time was prolonged in aged male rats, though this was not seen in the females Irvine et al (1974),. studying elderly humans, showed some evidence of reduced hydroxylation of amylobarbitone, and Jori, Di Salle & Quadri (1972) found similar results with aminopyrine O'Malley et al (1971).…”
mentioning
confidence: 91%
“…Such an increase could result from decreased efficiency of drug metabolizing enzymes. Reduced levels of cytochrome P-450 with advancing age has been directly demonstrated in rats (Kato & Takanaka, 1968a), and this decrease in in vitro enzyme activity is paralleled by impairment of drug metabolizing activity (Kato & Takanaka, 1968b (O'Malley, Crooks, Duke & Stevenson, 1971), and the rate of hydroxylation of amylobarbitone is reduced in the elderly (Irvine, Grove, Toseland & Trounce, 1974). Drugs may also accumulate as a result of impairment of renal function associated with advancing age (Shock, 1946).…”
Section: Introductionmentioning
confidence: 99%